Intraepithelial γδ T Cells May Bridge a Gap between Innate Immunity and Acquired Immunity to Herpes Simplex Virus Type 2 - Nishimura, Hitoshi (American Society for Microbiology, 2004)
Mice depleted of γδ T cells by in vivo administration of anti-TCRγδ monoclonal antibodies showed susceptibility against an intravaginal infection with herpes simplex virus type 2 (HSV-2). The systemic Th1 response was impaired in the γδ T-cell-depleted mice. Mice deficient in the Vδ1 T subset were susceptible to an intravaginal infection with HSV-2. Intraepithelial γδ T cells bearing Vδ1 may help protect against intravaginal infection with HSV-2 through promoting the systemic Th1 response.